Counterfactual Analysis of Runaway Volcanic Explosions - Aspinall, Willy; Woo, Gordon (Frontiers in Earth Science, 2019)
If your volcano is erupting, “The past is a nice place to visit, but certainly not a good place to stay…”. One of the major challenges in volcano crisis decision-making arises when unrest escalates and the threat could exist of a massive sudden eruption, despite information suggesting past eruptive activity had been more limited. Even a small chance of this happening may warrant an urgent call for evacuation. For most active volcanoes, there is only a very limited geological and historical record upon which to base an estimate of the chance of a massive eruption. However, this database may be expanded by stochastic modelling of past notable volcanic crises that had the dangerous potential but did not ultimately result in a massive eruption. The conceptual framework for the counterfactual analysis of runaway volcanic explosions is presented here, with reference to other extreme geohazards and georisks. This innovative type of probabilistic analysis has widespread application and is illustrated with the example of the well-documented 1997 Montserrat Vulcanian explosions sequence. An alternative possible mode of eruptive behaviour might have substituted this sequence with fewer but larger explosive eruptions or even by a single runaway extreme event. This latter contingency was considered at the time, and motivated a brief, temporary evacuation of the building then housing the Montserrat Volcano Observatory; in response to the escalating violence of explosions, the base for observatory operations was subsequently re-located much further away from the volcano.